Detection Of Sprague Dawley Sperm Using Matching Method. - Alias, Mohd Fauzi; Mat Isa, Nor Ashidi; Sulaiman, Siti Amrah; Zamli, Kamal Zuhairi (2008)

(untitled)
Cross correlation algorithm is the common method for image matching technique. In this paper, an expert system based on cross correlation is designed to reduce the workload of pathologist and improve the screening technology in medical field.